Implementation of Extreme Programming and Simple Additive Weighting for Web-Based Sales and Product Preference Analysis in Traditional Herbal Businesses - Sumardiono, Sumardiono; Priyadi, Wiwit; Wicaksono, Harjunadi; Santosa, Hadi; Sambath, Khoem; Liefalza, Andi Daffa (Institut Teknologi Dirgantara Adisutjipto, 2025)
The rapid development of information technology encourages UMKM to adopt digital solutions to improve business effectiveness. This study aims to design a web-based herbal medicine sales information system at UMKM Griya Jamoe Klasik using the Extreme Programming (XP) method and implementing the Simple Additive Weighting (SAW) algorithm to analyze the best-selling herbal medicine products. The research approach used is quantitative descriptive, with data collection methods through observation, interviews, and questionnaires to 10 respondents over a period of one week. The criteria used in the analysis include price, taste, efficacy, and texture, each given a certain weight. The results of the SAW algorithm application show that the